On the problem of objectivity: between rationality, representation and ideology - Borges Júnior, Eli (Ámbitos. Revista Internacional de Comunicación, 2019)
Despite all the contemporary discussion about the relativity of the points of view, the value of "objectivity" seems still quite present mainly in the narrative of the media about itself. In this article, we will try to demonstrate how this notion of "objectivity" can be reinterpreted, in the limit, as an ideological expression. For this, we will focus on the notion of "objectivity" problematized by the Brazilian philosopher Marilena Chaui. We will make a journey based on specific writings of the extensive work of the philosopher, writings that were revised and improved in different texts in the last years. Our path will present, at first, an overfly by the definition made by Chaui about the term "ideology", going to the theme of its relationship with the idea of "objectivity", especially in regard to the role of the "objectivity" in the construction of the "ideology". Such concepts are quite opportune in the reflection on the new arrangements of public sphere after the explosion of digital communications. Because of this, we conclude with a brief discussion about the actual and complex problem of the post-truth and "fake news". We assume here the ongoing character of our analysis, beyond the option for the definition of this specific cut as a way to present one within the innumerable possibilities of discussion of the controversial issue of objectivity.